1996
DOI: 10.1148/radiology.199.2.8668813
|View full text |Cite
|
Sign up to set email alerts
|

CT-guided transsternal core biopsy of anterior mediastinal masses.

Abstract: Computed tomography-guided transsternal biopsy was successful in 10 anterior mediastinal masses in 10 patients, with use of a coaxial length-matched bone biopsy system comprising an outer cannula and an inner eccentric drill bit. No complications occurred in nine of 10 biopsies (eight performed with an automatic cutting needle, two with a fine needle), with less discomfort than was caused by injection of anesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 0 publications
0
7
0
5
Order By: Relevance
“…Different techniques for CT-guided percutaneous needle biopsy of mediastinal lesions have been advocated. [58]…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques for CT-guided percutaneous needle biopsy of mediastinal lesions have been advocated. [58]…”
Section: Introductionmentioning
confidence: 99%
“…Very few cases of CT-guided transsternal mediastinal lesion biopsy have been reported in the literature (1)(2)(3)(4) . Astrom et al (1) reported 10 transsternal biopsies in which he used a bone biopsy system to penetrate the sternum.…”
Section: Discussionmentioning
confidence: 99%
“…Lezyonun tam lokalizasyonunu ve iğnenin hedef lezyona ulaştığını BT daha iyi gösterir. BT ile çok küçük lezyonlara biyopsi yapmak mümkündür ve vasküler yaralanma gibi komplikasyon olasılığı düşüktür (25)(26)(27)(28)(29)(30).…”
Section: Klinikunclassified